EFFECTIVENESS OF WOOLWICH MASSAGE ON BREAST MILK INTAKE AND INFANT WEIGHT GAIN IN POSTPARTUM MOTHERS - Etik Khusniyati (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Lactation problems during the early postpartum period, such as delayed onset of lactation and breast engorgement, frequently trigger excessive neonatal weight loss and increase the risk of exclusive breastfeeding failure, which predisposes infants to stunting. This study aimed to analyze the effectiveness of the Woolwich Massage intervention on increasing breast milk intake and infant weight gain among postpartum mothers. Method:This quasi-experimental study using a non-equivalent control group design with pre-test and post-test involved 26 postpartum mothers in the Gebangmalang village and Tambakagung village, selected through purposive sampling (13 in the intervention group and 13 in the control group). Breast milk intake was measured using the test weighing method, and infant weight was recorded before and after a 5-day intervention period. The Wilcoxon Signed Rank Test showed that the intervention group experienced a significant increase in mean breast milk intake by 28.9 ml and a significant mean infant weight gain of 190.8 grams, with respective significance values of p-value = 0.001 (p<0.05). Woolwich Massage effectively stimulates the lactiferous sinuses mechanically and hormonally to trigger prolactin release and optimize breast emptying. This complementary therapy is proven effective in optimizing early neonatal nutritional fulfillment and supporting ideal physical growth.